Cardiac impact of R-wave triggered irreversible electroporation therapy - Kostrzewa, Michael; Tueluemen, Erol; Rudic, Boris; Rathmann, Nils-Andreas; Akın, Ibrahim; Henzler, Thomas; Liebe, Volker; Schönberg, Stefan; Borggrefe, Martin; Diehl, Steffen J. (Heart rhythm, 2018)
Irreversible electroporation (IRE) is a novel tumor ablative therapy technique, using electric fields to induce apoptosis in target tissues. Whether these electric pulses of high field strength can cause cardiac damage and/or ablation-induced arrhythmias is unclear. The purpose of this study was to systematically evaluate the safety of electrocardiogram (ECG)-gated IRE with regard to cardiac side effects.